2009
DOI: 10.1007/s11689-009-9037-4
|View full text |Cite
|
Sign up to set email alerts
|

Speech delays and behavioral problems are the predominant features in individuals with developmental delays and 16p11.2 microdeletions and microduplications

Abstract: Microdeletions and microduplications encompassing a ~593-kb region of 16p11.2 have been implicated as one of the most common genetic causes of susceptibility to autism/autism spectrum disorder (ASD). We report 45 microdeletions and 32 microduplications of 16p11.2, representing 0.78% of 9,773 individuals referred to our laboratory for microarray-based comparative genomic hybridization (aCGH) testing for neurodevelopmental and congenital anomalies. The microdeletion was de novo in 17 individuals and maternally i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
159
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(177 citation statements)
references
References 22 publications
11
159
0
1
Order By: Relevance
“…Premature balding, present in the previously reported family, was not present in our cohort, which may be due to the relative younger ages of the subjects. Similar to other genomic disorders that have heterogeneous clinical phenotypes, [34][35][36] our cohort displays phenotypic variability. In addition, there have been healthy carriers of this microduplication in the family reported by Grisart et al 22 and in a father in our cohort.…”
Section: Discussionmentioning
confidence: 57%
“…Premature balding, present in the previously reported family, was not present in our cohort, which may be due to the relative younger ages of the subjects. Similar to other genomic disorders that have heterogeneous clinical phenotypes, [34][35][36] our cohort displays phenotypic variability. In addition, there have been healthy carriers of this microduplication in the family reported by Grisart et al 22 and in a father in our cohort.…”
Section: Discussionmentioning
confidence: 57%
“…For some human CNV-associated syndromes such as 7q11.23 deletion (i.e., Williams-Beuren syndrome) and the reciprocal duplication (42), loss and gain are associated with opposing clinical features. Indeed, this is the case for head size alterations associated with 16p11.2 CNVs (16), but certainly not for behavioral symptoms of these patients (10,13,16). In mice, we see that loss and gain of 16p11.2 cause distinct and opposing behavioral phenotypes.…”
Section: Resultsmentioning
confidence: 82%
“…Several human studies compared the behavioral symptoms of patients with 16p11.2 deletions and duplications (10,13,16); however, to our knowledge, there is no evidence that loss and gain of 16p11.2 affect behavior in opposing ways. Even with patients harboring the same 16p11.2 lesion, there is a broad spectrum of clinical symptoms, some patients being severely affected and others highly functional.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Another study reported 'speech retardation' (p.85) in 19 of 20 (95%) patients with 16p11.2 deletions. 8 Other studies have found speech and language deficits in 17 of 18 (94%) patients with 16p11.2 deletions, 9 and language deficits in 18 of 21 (86%) patients. 4 In a study reporting developmental milestones for speech-language acquisition in 9 patients with 16p11.2 deletions, 6 (67%) patients had significant delays in age of single word acquisition, 7 (78%) had delays in age of phrase development, and all 9 (100%) had deficits in reciprocal conversation.…”
Section: Introductionmentioning
confidence: 94%